Salmonella spp. contamination in commercial layer hen farms using different types of samples and detection methods - Soria, M C (2017)
Fil: Soria, M C. Instituto Nacional de Tecnología Agropecuaria EEA Concepción del Uruguay, Ruta Provincial 39 Km 143,5, 3260, Concepción del Uruguay, Entre Ríos; Argentina.